Risk of musculoskeletal disorders in female farmers and its socioeconomic determinants in Kashmir valley - Aisha Dev; M. Imran Ganaie; Ishtiaq A. Mayer; Harmeet Singh (Clinical Epidemiology and Global Health)
Background/aims: This study investigates the prevalence of musculoskeletal disorders (MSDs) among female farmers, both perennial and non-perennial, in the Kashmir Valley, India. Given the manual labour intensive nature of agriculture in India, MSDs are a significant concern, often stemming from repetitive and constrained postures adopted during farming activities. Methods: Utilizing a cross-sectional design, data was collected through a questionnaire comprising two parts: the Nordic Musculoskeletal Questionnaire (NMQ) for self-reporting MSDs and the second part dealing with socio-economic parameters. Participants were recruited randomly using a three-stage sampling technique from the working age group of 18 years to up to 60 years, resulting in 293 respondents (comprising 66.14 % perennial and 33.86 % non-perennial farmers). Results: The overall prevalence of MSDs was found to be 74.74 %, with a notable majority of perennial cultivators (95.3 %) reporting MSDs. Activities performed by female farmers were frequently characterized by repetitive and constrained postures, with the lower back being the most commonly affected site (68.78 %), followed by the neck/shoulders (62.94 %) and elbows/hands (13.54 %). Multinomial logistic regression analysis revealed age and marital status as significant risk factors for lower back disorders, neck/shoulders, and elbows/hands (p < 0.05), with workplace environment emerging as an additional risk factor for elbows/hands. Conclusion: The high prevalence of MSDs amongst the respondents establishes the urgent need for preventive strategies and educational programs aimed at promoting ergonomics awareness among female farmers.